2019 Joint Conference of the IEEE International Frequency Control Symposium and European Frequency and Time Forum (EFTF/IFC) 2019
DOI: 10.1109/fcs.2019.8856070
|View full text |Cite
|
Sign up to set email alerts
|

Light-Shift Suppression with Novel Variants of Adaptive Ramsey Spectroscopy

Abstract: We present a brief review of the rapidly growing field of autobalanced Ramsey spectroscopy followed by a detailed discussion and review of two novel techniques that were developed and tested in our laboratory: displaced frequency-jump Ramsey spectroscopy and combined error signal spectroscopy. These two techniques are related to, yet different from autobalanced Ramsey spectroscopy. The use of these techniques in a cold-atom clock based on coherent population trapping has reduced instabilities from variations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…[19,20] Recently, numerous theoretical and experimental studies of optical Ramsey spectrum have shown that the modified Ramsey spectrum can also improve the accuracy of optical clocks by sharply reducing the probe Stark shift by hyper-Ramsey spectrum or autobalanced Ramsey spectroscopy. [21][22][23][24][25][26][27][28] Surprisingly, there are few reports about the optical Ramsey spectrum in optical lat-tice clocks and few papers on detailed study of the stability in optical lattice clocks based on the Rabi or Ramsey spectra, although the optical Ramsey spectrum has been successfully applied in optical lattice clocks. [16] In this paper, we experimentally demonstrate the optical Ramsey spectrum in an 87 Sr optical lattice clock using a two π/2-pulse excitation scheme.…”
Section: Introductionmentioning
confidence: 99%
“…[19,20] Recently, numerous theoretical and experimental studies of optical Ramsey spectrum have shown that the modified Ramsey spectrum can also improve the accuracy of optical clocks by sharply reducing the probe Stark shift by hyper-Ramsey spectrum or autobalanced Ramsey spectroscopy. [21][22][23][24][25][26][27][28] Surprisingly, there are few reports about the optical Ramsey spectrum in optical lat-tice clocks and few papers on detailed study of the stability in optical lattice clocks based on the Rabi or Ramsey spectra, although the optical Ramsey spectrum has been successfully applied in optical lattice clocks. [16] In this paper, we experimentally demonstrate the optical Ramsey spectrum in an 87 Sr optical lattice clock using a two π/2-pulse excitation scheme.…”
Section: Introductionmentioning
confidence: 99%